Specificity of presenilin‐1‐ and presenilin‐2‐dependent γ‐secretases towards substrate processing. Issue 2 (10th October 2017) - Stanga, Serena; Vrancx, Céline; Tasiaux, Bernadette; Marinangeli, Claudia; Karlström, Helena; Kienlen‐Campard, Pascal
Abstract: The two presenilin‐1 (PS1) and presenilin‐2 (PS2) homologs are the catalytic core of the γ‐secretase complex, which has a major role in cell fate decision and Alzheimer's disease (AD) progression. Understanding the precise contribution of PS1‐ and PS2‐dependent γ‐secretases to the production of β‐amyloid peptide (Aβ) from amyloid precursor protein (APP) remains an important challenge to design molecules efficiently modulating Aβ release without affecting the processing of other γ‐secretase substrates. To that end, we studied PS1‐ and PS2‐dependent substrate processing in murine cells lacking presenilins (PSs) (PS1KO, PS2KO or PS1‐PS2 double‐KO noted PSdKO) or stably re‐expressing human PS1 or PS2 in an endogenous PS‐null (PSdKO) background. We characterized the processing of APP and Notch on both endogenous and exogenous substrates, and we investigated the effect of pharmacological inhibitors targeting the PSs activity (DAPT and L‐685, 458). We found that murine PS1 γ‐secretase plays a predominant role in APP and Notch processing when compared to murine PS2 γ‐secretase. The inhibitors blocked more efficiently murine PS2‐ than murine PS1‐dependent processing. Human PSs, especially human PS1, expression in a PS‐null background efficiently restored APP and Notch processing. Strikingly, and contrary to the results obtained on murine PSs, pharmacological inhibitors appear to preferentially target human PS1‐ than human PS2‐dependent γ‐secretase activity.